A factor analysis of Malaysian youth lifestyle domain - Lai, Che Ching; Hamisah Hasan; Jamali Samsuddin (Universiti Malaysia Sabah, 2020)
This study was conducted to validate the 15 items that were newly developed to measure youth lifestyle within the context of Malaysian society. It is indeed essential to examine the relevancy of the items from the scope of the Malaysian culture since most of the tools in measuring lifestyle originated from outside the context of Malaysian society. An exploratory factor analysis was applied in order to generate simpler and more explicitly defined constructs to classify the lifestyles of youth based on Malaysian respondents. The result shows that there were only 9 items of the scale used to measure youth lifestyle in Malaysia. The 6 items that were initially used were dropped from the total items due to the lower than expected score for commonalities. There were five proposed initial domains which were reduced to three domains. The justification of the new dimensions and implications of the findings are discussed